Cancers in Australia in 2010 attributable to modifiable factors: Introduction and overview - Whiteman, D.; Webb, P.; Green, A.; Neale, R.; Fritschi, L.; Bain, C.; Parkin, D.; Wilson, L.; Olsen, C.; Nagle, C.; Pandeya, N.; Jordan, S.; et al. (Wiley-Blackwell, 2015)
Objective: To describe the approach underpinning a national project to estimate the numbers and proportions of cancers occurring in Australia in 2010 that are attributable to modifiable causal factors. Methods: We estimated the population attributable fraction (PAF) (or prevented fraction) of cancers associated with exposure to causal (or preventive) factors using standard formulae. Where possible, we also estimated the potential impact on cancer incidence resulting from changes in prevalence of exposure. Analyses were restricted to factors declared causal by international agencies: tobacco smoke; alcohol; solar radiation; infectious agents; obesity; insufficient physical activity; insufficient intakes of fruits, vegetables and fibre; red and processed meat; menopausal hormone therapy (MHT); oral contraceptive pill (OCP); and insufficient breast feeding. Separately, we estimated numbers of cancers prevented by: aspirin; sunscreen; MHT; and OCP use. We discuss assumptions pertaining to latent periods between exposure and cancer onset, choices of prevalence data and risk estimates, and approaches to sensitivity analyses. Results: Numbers and population attributable fractions of cancer are presented in accompanying papers. Conclusions: This is the first systematic assessment of population attributable fractions of cancer in Australia.